Single-layer eggshell-shaped nitrogen-sulfur co-doped monatomic cobalt catalyst as well as preparation method and application thereof
By introducing an asymmetric Co-S/Co-N coordination structure on the SiO2 substrate, a single-layer eggshell-like nitrogen-sulfur co-doped single-atom cobalt catalyst was prepared, which solved the problem of insufficient activation efficiency and stability of existing catalysts, and achieved efficient and stable degradation of antibiotics in water.
Patent Information
- Application Number
- CN202411937402.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The existing single-atom cobalt catalysts are difficult to meet the actual requirements in terms of efficiency and stability of activated peracetic acid, and cannot effectively degrade antibiotic pollution in water.
SiO2 is used as the substrate and an asymmetric Co-S/Co-N coordination structure is introduced to prepare a single-layer eggshell-like nitrogen-sulfur co-doped single-atom cobalt catalyst. By calcining and etching SiO2, a thin shell morphology is formed to maximize the utilization of metal catalytic sites.
It significantly improves the activation performance and stability of the catalyst, can efficiently and stably degrade a variety of antibiotics in water, and maintains high efficiency after multiple recycling, avoiding secondary pollution.
Smart Images

Figure CN119733547A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water pollution control, and in particular to a single-layer eggshell-shaped nitrogen-sulfur co-doped single-atom cobalt catalyst and a preparation method and application thereof. Background Art
[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] As a typical emerging pollutant, antibiotics are widely used in large quantities and in a wide range of applications. They are widely detected in natural water environments. Although the current exposure level of antibiotics in the environment is low, their structure is stable and they have bioaccumulation and amplification effects. Their potential harm to the ecosystem cannot be ignored. Given the complex sources and components of antibiotic pollution in water bodies, wastewater treatment needs to purify specific types of wastewater in a targeted and sustainable manner to achieve precise oxidative degradation of trace antibiotics in different water environments. Therefore, it is imperative to develop selectively adjustable treatment technologies.
[0004] Advanced oxidation techniques (AOPs) rely on the in-situ generation of strong oxidizing active substances, which can efficiently degrade antibiotics or even completely mineralize them. Therefore, AOPs are widely used in the treatment of antibiotic pollution. In recent years, the peracetic acid (PAA) advanced oxidation technology (PAA-AOPs) based on the in-situ generation of organic free radicals (RO·) has attracted the attention of more and more researchers. Due to its advantages such as simple operation, low cost and few toxic by-products, it has shown great potential in the field of water remediation. In addition, compared with the inorganic free radical active substances (such as ·OH, SO 4 · - ), RO has a longer survival time and is less affected by the complex matrix of the water body, so it has a stronger selective degradation ability for new antibiotic pollutants.
[0005] The construction of new and efficient catalytic systems is the main research direction of PAA advanced oxidation technology. Its core lies in the development of highly active and highly stable heterogeneous catalysts to improve the efficiency of active substances. Single atom catalysts (SACs) are a new type of catalysts, consisting of isolated metal atoms anchored on appropriate carriers. At present, the application of SACs to activate PAA is still in its infancy. The reported single atom cobalt catalysts (Co-SACs) are difficult to meet the actual requirements in terms of activation efficiency and catalyst stability. Therefore, it is urgent to further regulate Co-SACs to enhance their activity and stability, and provide theoretical and technical support for the promotion and application of PAA advanced oxidation technology. Summary of the invention
[0006] In view of this, the present invention provides a single-layer eggshell-shaped nitrogen-sulfur co-doped single-atom cobalt catalyst and its preparation method and application. 2 Taking the raw materials as the base and introducing the asymmetric Co-S / Co-N coordination structure, the performance of traditional Co-SACs in activating PAA was significantly enhanced, and the infiltration of cobalt ions during the activation process was effectively inhibited. Therefore, no secondary pollution would be generated during the catalytic process, and the extremely high catalytic efficiency could be maintained after multiple cycles, thus achieving efficient, stable and continuous degradation of organic pollutants.
[0007] In a first aspect, the present invention provides a method for preparing a single-layer eggshell-shaped nitrogen-sulfur co-doped single-atom cobalt catalyst, comprising the following steps:
[0008] Dissolve 1-allyl-2-thiourea and cobalt salt in water and add SiO 2 Nanospheres, heated and stirred, and the precursor was obtained after evaporation of the solvent;
[0009] The precursor is calcined under inert gas protection, and SiO is etched after calcination. 2 , then pickled with acid, washed and dried to obtain the product.
[0010] In a second aspect, the present invention provides a single-layer eggshell-shaped nitrogen-sulfur co-doped single-atom cobalt catalyst prepared by the above preparation method.
[0011] In a third aspect, the present invention provides the use of the above-mentioned single-layer eggshell-shaped nitrogen-sulfur co-doped single-atom cobalt catalyst in activating peracetic acid to degrade organic pollutants.
[0012] Compared with the prior art, the present invention has achieved the following beneficial effects:
[0013] (1) The preparation process of the single-layer eggshell-shaped nitrogen-sulfur co-doped single-atom cobalt catalyst of the present invention is based on SiO 2 Nanospheres were used as substrate templates, and an asymmetric Co-S / Co-N coordination structure was introduced by calcination with cobalt salts and 1-allyl-2-thiourea. The introduction of the asymmetric coordination structure can cause significant delocalized electrons around the Co center, thereby promoting the adsorption of PAA and the cleavage of the OO bond. The asymmetric electronic structure also generates an additional local electric field, which is beneficial to the cleavage of the OH bond in PAA through the proton-coupled electron transfer pathway. 2It not only plays a key role in the formation of the eggshell-like morphology of the catalyst, but also provides abundant coordination sites for single atomic cobalt. The single-layer eggshell-like thin shell structure is conducive to maximizing the utilization of metal catalytic sites and promoting the contact between Co-S / Co-N sites and PAA and pollutants. The internal cavity can enhance the removal efficiency of pollutants through the confinement effect. At the same time, the preparation method of the present invention can obtain a higher loading amount of single atomic cobalt, which can reach about 10wt%.
[0014] (2) The single-layer eggshell-shaped nitrogen-sulfur co-doped single-atom cobalt catalyst of the present invention can catalyze the decomposition of peracetic acid to generate a variety of active oxygen species in situ, including ·OH, RO· and singlet oxygen ( 1 O 2 ), can achieve efficient degradation of multiple antibiotics in sewage, and can achieve a degradation rate of sulfamethoxazole of more than 95% within 2 minutes at the fastest. In addition, the catalyst does not produce secondary pollution during the catalytic process, and can still maintain extremely high catalytic efficiency after multiple recycling. The nitrogen-sulfur co-doped single-atom cobalt catalyst prepared by the present invention can catalyze the activation of peracetic acid to degrade antibiotics in sewage in a near-neutral environment. In actual treatment, it is not necessary to add acid or alkali to adjust the pH, thereby reducing economic costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0016] Figure 1 This is a scanning electron microscope (SEM) image of the nitrogen-sulfur co-doped single-atom cobalt catalyst prepared in Example 1 of the present invention;
[0017] Figure 2 This is an element scanning image of the nitrogen-sulfur co-doped single-atom cobalt catalyst prepared in Example 1 of the present invention under SEM mode;
[0018] Figure 3 This is a spherical aberration correction-high angle annular dark field-scanning transmission electron microscopy (HAADF-STEM) image of the nitrogen-sulfur co-doped single-atom cobalt catalyst prepared in Example 1 of the present invention;
[0019] Figure 4 The effect of activating peracetic acid to degrade sulfamethoxazole using single-atom cobalt catalysts of Examples 1-2 and Comparative Examples 1-2 is compared;
[0020] Figure 5 The single-atom cobalt catalyst of Examples 1, 3-4 of the present invention is used to activate peracetic acid to degrade sulfamethoxazole;
[0021] Figure 6 The effects of activating peracetic acid and degrading sulfamethoxazole using single-atom cobalt catalysts of Examples 1 and 5 of the present invention and Comparative Examples 3 to 4 are compared;
[0022] Figure 7 The single-atom cobalt catalyst of Examples 1, 6 to 7 of the present invention is used to activate peracetic acid to degrade sulfamethoxazole;
[0023] Figure 8 This is a diagram showing the removal effect of sulfamethoxazole by activating peracetic acid with the single-atom cobalt catalyst prepared in Example 1 under different pH conditions of the present invention;
[0024] Fig. 9 This is a diagram showing the effect of activating peracetic acid to degrade sulfamethoxazole using different addition amounts of single-atom cobalt catalyst in Example 1 of the present invention;
[0025] Fig.10 This is a diagram showing the removal effect of sulfamethoxazole by activating peracetic acid in systems with different peracetic acid concentrations according to the present invention;
[0026] Fig.11 This is a diagram showing the effect of activating a peracetic acid system using a single atom cobalt catalyst according to Example 1 of the present invention to degrade various pollutants;
[0027] Fig.12 This is the recycling effect of the single-atom cobalt catalyst in Example 1 of the present invention. DETAILED DESCRIPTION
[0028] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0029] The present invention provides a method for preparing a single-layer eggshell-shaped nitrogen-sulfur co-doped single-atom cobalt catalyst, comprising the following steps:
[0030] Dissolve 1-allyl-2-thiourea and cobalt salt in water and add SiO 2 Nanospheres, heated and stirred, and the precursor was obtained after evaporation of the solvent;
[0031] The precursor is calcined under inert gas protection, and SiO is etched after calcination. 2 , then pickled with acid, washed and dried to obtain the product.
[0032] The present invention uses 1-allyl-2-thiourea as a sulfur source and a nitrogen source, and reacts with cobalt salt and SiO 2 During the calcination process of the nanospheres, SiO 2An asymmetric Co-S / Co-N coordination structure was introduced on the substrate, and Co was distributed in the form of single atoms. 2 A single-layer eggshell-like thin shell morphology is formed, which can maximize the utilization of metal catalytic sites, thereby promoting the contact between Co-S / Co-N sites and PAA and pollutants, and the internal cavity can enhance the removal efficiency of pollutants through the confinement effect. The single atomic cobalt loading in the catalyst prepared by the above method of the present invention can reach about 10wt%, with a high single atomic cobalt loading.
[0033] In the present invention, the cobalt salt is selected from cobalt nitrate, cobalt chloride or cobalt sulfate. In practical applications, hydrated salts of the above cobalt salts can be selected, and the present invention does not impose any particular restrictions on this. The selection of cobalt salt will affect the catalytic effect to a certain extent, and cobalt nitrate is more preferred in the present invention.
[0034] In the present invention, the molar ratio of the cobalt salt to 1-allyl-2-thiourea is 1:(15-35); the molar ratio of the two will also have an impact on the final catalytic effect. Too much cobalt salt will have an adverse effect on the dispersibility of single-atom cobalt, and too little cobalt salt will lead to too few metal active sites, both of which will reduce the catalytic activity. The dosage ratio of the 1-allyl-2-thiourea to water is 1g:(3-10)mL, and water is used as a solvent to dissolve the cobalt salt and 1-allyl-2-thiourea and fully mix the two; at the same time, as SiO 2 The dispersing solvent is mixed with the cobalt salt and 1-allyl-2-thiourea in the solution. 2 The mass ratio of the nanospheres is 0.08:(0.5-2), and more preferably 0.08:(0.8-1.2).
[0035] The present invention is to SiO 2 The preparation method of the nanospheres is not particularly limited. The present invention preferably adopts the Stober method for preparation. Those skilled in the art can obtain SiO 2 Nanospheres, SiO 2 The particle size of the nanospheres is 100 to 300 nm.
[0036] In the present invention, the heating and stirring temperature is 60-90°C, and the heating and stirring time is 60-180 minutes; the temperature of evaporating the solvent is 50-70°C, and the specific time required depends on the complete evaporation of the solvent, which is not particularly limited in the present invention.
[0037] In the present invention, the inert gas is selected from nitrogen or argon, more preferably argon.
[0038] In the present invention, the calcination temperature is 850-1000°C, more preferably 900-1000°C. Too high or too low a calcination temperature will affect the activity of the prepared catalyst; the calcination time is 2-4 hours. The time for heating to the calcination temperature is preferably 2-8°C / min.
[0039] In the present invention, the etching SiO 2 The method is to use sodium hydroxide or potassium hydroxide solution for etching, which has a lower etching risk; the concentration of the sodium hydroxide or potassium hydroxide solution is 3 to 8 mol / L.
[0040] In the present invention, the acid leaching process uses hydrochloric acid or sulfuric acid solution with a concentration of 0.05 to 0.5 mol / L. The acid leaching process can neutralize the alkali in the aforementioned etching process on the one hand, and remove the residual metal cobalt on the surface of the catalyst (monoatomic cobalt does not react with acid) on the other hand. The acid leaching time is 40 to 120 minutes. After the acid leaching is completed, water and ethanol are used for washing, and then drying is performed. The present invention does not impose special restrictions on the drying process. The present invention is preferably vacuum dried at 50 to 80°C.
[0041] The present invention also provides a single-layer eggshell-shaped nitrogen-sulfur co-doped single-atom cobalt catalyst prepared by the above preparation method, wherein the loading amount of the single-atom cobalt is about 10wt%.
[0042] The present invention also provides the use of the above-mentioned single-layer eggshell-shaped nitrogen-sulfur co-doped single-atom cobalt catalyst in activating peracetic acid to degrade antibiotics. In the single-layer eggshell-shaped nitrogen-sulfur co-doped single-atom cobalt catalyst provided by the present invention, the introduction of the Co-S / Co-N asymmetric coordination structure can cause significant delocalized electrons around the Co center, thereby promoting the adsorption of PAA and the cleavage of the OO bond. The asymmetric electronic structure also generates an additional local electric field, which is beneficial to the cleavage of the OH bond in PAA through the proton-coupled electron transfer pathway; the single-layer eggshell-shaped thin shell structure promotes the contact of the Co-S / Co-N site with PAA and pollutants, and the internal cavity can enhance the removal efficiency of pollutants through the confinement effect. The catalyst can catalyze the decomposition of peracetic acid to generate a variety of active oxygen species in situ, including ·OH, RO· and singlet oxygen ( 1 O 2 ), which can achieve efficient degradation of a variety of antibiotics in sewage, including sulfamethoxazole (SMX), sulfadiazine (SDZ), sulfadimethoxine (SDM), sulfamethoxazole (SMIZ), ciprofloxacin (CIP), enrofloxacin (ENF), tetracycline (TTC), 4-chlorophenol (4-CP) and phenol (PN).
[0043] In the present invention, the ratio of the monolayer eggshell-shaped nitrogen-sulfur co-doped single-atom cobalt catalyst, peracetic acid, and organic pollutants is (50-150) mg: (0.2-0.6) mmol: (1-15) μmol; the concentration of the monolayer eggshell-shaped nitrogen-sulfur co-doped single-atom cobalt catalyst is 50-150 mg / L. The pH of the application process is 5-8, more preferably 6-7.
[0044] The technical solution of the present invention is further described below in conjunction with specific examples. The present invention has no special restrictions on the sources of the reagents used in the following examples, and commercial products known to those skilled in the art can be used. The room temperature or normal temperature in the following examples is 25±3°C.
[0045] In the following examples, SiO 2 The preparation method of nanospheres is as follows: 6 mL of tetraethyl orthosilicate (TEOS) is added to 210 mL of anhydrous ethanol and stirred continuously. Then 7.2 mL of ammonium hydroxide (25 wt%) and 42 mL of deionized water are added dropwise to the above solution. The above mixed solution is stirred at room temperature for 24 hours to form a white suspension. Subsequently, a centrifuge is used to separate the solid precipitate at 8500 rpm for 5 minutes, and it is washed 3 times with deionized water and ethanol. Finally, it is dried in a vacuum oven at 65 ° C for 12 hours to obtain SiO 2 Nanospheres, average particle size is 200nm.
[0046] Example 1
[0047] This embodiment provides a method for preparing a nitrogen-sulfur co-doped single-atom cobalt catalyst.
[0048] (1) 1.0 g of 1-allyl-2-thiourea (8.62 mmol) and 80 mg of Co(NO 3 ) 2 6H 2 O (0.27mmol, namely 1-allyl-2-thiourea and Co (NO 3 ) 2 6H 2 O (molar ratio of 32:1) was added to 5 mL of deionized water and stirred to form a clear solution, and then 1.0 g SiO 2 Nanospheres were prepared and stirred in a beaker at 80 °C for 2 h, and the precursor was obtained by slowly evaporating the solvent in an oven at 60 °C.
[0049] (2) The precursor of step (1) was heated to 900° C. at a heating rate of 5° C. / min under an argon atmosphere and calcined for 3 h to obtain a calcined product.
[0050] (3) After the calcined product was naturally cooled to room temperature, 5 mol / L NaOH solution was used to remove SiO2 The nanosphere template was acid-leached in 0.1 M hydrochloric acid for 60 min to remove the residual metal, then washed with deionized water and ethanol three times respectively, and dried in a vacuum oven at 65 °C for 12 h to obtain the nitrogen-sulfur co-doped single-atom cobalt catalyst (denoted as Co SA -CNS).
[0051] Figure 1 This is a scanning electron microscope (SEM) image of the nitrogen-sulfur co-doped single-atom cobalt catalyst prepared in this example; Figure 1 It can be seen that the prepared single-atom cobalt catalyst presents a typical single-layer thin shell spherical structure.
[0052] Figure 2 This is an element scanning (EDX) characterization image of the nitrogen-sulfur co-doped single-atom cobalt catalyst prepared in this example under SEM mode. Figure 2 It can be seen that Co, C, N and S elements are widely distributed in the catalyst, and the Co loading is further measured to be 11.2 wt %, which is similar to the inductively coupled plasma optical emission spectrometer (ICP-OES) test result (10.8 wt %).
[0053] Figure 3 This is a spherical aberration correction-high angle annular dark field-scanning transmission electron microscope (HAADF-STEM) image of the nitrogen-sulfur co-doped single-atom cobalt catalyst prepared in this example; Figure 3 It can be seen that the active metal sites are dispersed in a single atom manner and have a high loading density.
[0054] Example 2
[0055] This embodiment provides a method for preparing a single-layer eggshell-shaped nitrogen-sulfur co-doped single-atom cobalt catalyst.
[0056] (1) 1.0 g of 1-allyl-2-thiourea (8.62 mmol) and 157 mg of Co(NO 3 ) 2 6H 2 O (0.54mmol, namely 1-allyl-2-thiourea and Co (NO 3 ) 2 6H 2 O (molar ratio of 16:1) was added to 5 mL of deionized water and stirred to form a clear solution, and then 1.0 g SiO 2 Nanospheres were prepared and stirred in a beaker at 80 °C for 2 h, and the precursor was obtained by slowly evaporating the solvent in an oven at 60 °C.
[0057] (2) The precursor of step (1) was heated to 900° C. at a heating rate of 5° C. / min under an argon atmosphere and calcined for 3 h to obtain a calcined product.
[0058] (3) After the calcined product was naturally cooled to room temperature, 5 mol / L NaOH solution was used to remove SiO 2 The nanosphere template was acid-leached in 0.1 M hydrochloric acid for 60 min to remove the residual metal, and then washed with deionized water and ethanol three times respectively, and dried in a vacuum oven at 65 ° C for 12 h to obtain a single-layer eggshell-like nitrogen-sulfur co-doped single-atom cobalt catalyst (Co SA -CNS).
[0059] Example 3
[0060] The difference between this embodiment and embodiment 1 is that the SiO 2 The amount of nanospheres added was 0.5 g.
[0061] Example 4
[0062] The difference between this embodiment and embodiment 1 is that the SiO 2 The amount of nanospheres added was 2 g.
[0063] Example 5
[0064] The difference between this embodiment and embodiment 1 is that the calcination temperature of this embodiment is 1000°C.
[0065] Example 6
[0066] Compared with Example 1, the difference between this embodiment and Example 1 is that this embodiment uses CoCl 2 6H 2 O (67 mg, 0.28 mmol) to replace Co(NO 3 ) 2 6H 2 O.
[0067] Example 7
[0068] The difference between this embodiment and embodiment 1 is that this embodiment adopts CoSO 4 7H 2 O (79 mg, 0.28 mmol) to replace Co(NO 3 ) 2 6H 2 O.
[0069] Comparative Example 1
[0070] Compared with Example 1, the difference between this comparative example is that Co(NO 3 ) 2 6H 2The amount of O added was 39 mg (0.134 mmol), that is, 1-allyl-2-thiourea and Co(NO 3 ) 2 6H 2 The molar ratio of O is 64:1.
[0071] Comparative Example 2
[0072] Compared with Example 1, the difference between this comparative example is that Co(NO 3 ) 2 6H 2 The amount of O added was 314 mg (1.08 mmol), that is, 1-allyl-2-thiourea and Co(NO 3 ) 2 6H 2 The molar ratio of O is 8:1.
[0073] Comparative Example 3
[0074] The difference between this comparative example and Example 1 is that the calcination temperature of this comparative example is 700°C.
[0075] Comparative Example 4
[0076] The difference between this comparative example and Example 1 is that the calcination temperature of this comparative example is 800°C.
[0077] Test example
[0078] 1. Performance measurement of catalyst-activated peracetic acid for degradation of sulfamethoxazole in Examples 1 to 7 and Comparative Examples 1 to 4:
[0079] Peracetic acid was added to wastewater containing sulfamethoxazole (SMX) at a concentration of 10 μM to make its concentration reach 0.26 mM, and the pH value of the wastewater was adjusted to 7.0 with 0.1 mM sulfuric acid or 0.1 mM sodium hydroxide solution. The single-atom cobalt catalyst prepared in Examples 1 to 7 and Comparative Examples 1 to 4 was added to the above solution to make its concentration reach 50 mg / L, and the reaction was stirred at room temperature for 5 minutes, and the removal rate of sulfamethoxazole over time was recorded.
[0080] The removal rate results of Examples 1-2 and Comparative Examples 1-2 are as follows: Figure 4 As shown, it can be seen that the molar ratio of the cobalt salt to 1-allyl-2-thiourea has a significant effect on the removal rate. When the cobalt salt content is too high (Comparative Example 1), the removal rate of 5 min is 81%. This may be because the high proportion of cobalt salt causes a large amount of cobalt ions to agglomerate on the surface of silica, affecting the dispersibility of cobalt; when the cobalt salt content is too low, there are too few metal sites, and the removal rate of 5 min is only 68%; while the removal rates of Example 1 and Example 2 at 2 min have both reached 90%, and the removal rates of 5 min have both reached 100%.
[0081] The removal rate results of Examples 1, 3 to 4 are as follows Figure 5 As shown, it can be seen that SiO 2 The amount of template also affects the final removal efficiency. The optimal value is achieved when the added amount is 0.1g, and the removal rate can reach 100% within 5 minutes.
[0082] The removal rate results of Examples 1, 5 and Comparative Examples 3 to 4 are as follows: Figure 6 As shown, it can be seen that when the temperature is too low (Comparative Example 3-700°C, Comparative Example 4-800°C), the removal efficiency is not high, and the removal rate within 5 minutes is less than 80%. This is mainly because the pyrolysis temperature is too low, making it difficult for cobalt atoms to be completely dispersed.
[0083] The removal rate results of Examples 1, 6 to 7 are as follows Figure 7 As shown, it can be seen that different types of cobalt salts will also have a certain impact on the degradation rate. The catalytic performance of the catalyst prepared by cobalt nitrate in Example 1 is the best. This may be because the complex structures formed by the reaction of different cobalt salts with 1-allyl-2-thiourea are different, which in turn affects the local coordination environment of the prepared cobalt single atom, thereby affecting its catalytic performance.
[0084] 2. Degradation experiment at different pH values:
[0085] Peracetic acid was added to wastewater containing 10 μM sulfamethoxazole to make its concentration reach 0.26 mM, and the pH value of the wastewater was adjusted to 4.0-10.0 with 0.1 mM sulfuric acid or 0.1 mM sodium hydroxide solution, which were 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, and 10.0, respectively. The single-atom cobalt catalyst prepared in Example 1 was added to the above solution to make its concentration reach 50 mg / L, and the reaction was stirred at room temperature for 5 minutes. The removal rate of sulfamethoxazole over time was as follows: Figure 8 shown.
[0086] from Figure 8It can be seen that when the pH value of the sewage is 4.0, after 5 minutes of reaction at room temperature, it is found that the removal rate of sulfamethoxazole in the peracetic acid system activated by the single-atom cobalt catalyst is 67%. When the pH value of the sewage is 5.0, after 5 minutes of reaction at room temperature, it is found that the removal rate of sulfamethoxazole in the peracetic acid system activated by the single-atom cobalt catalyst is 88%. When the pH value of the sewage is 6.0, after 5 minutes of reaction at room temperature, it is found that the removal rate of sulfamethoxazole in the peracetic acid system activated by the single-atom cobalt catalyst is 99%. When the pH value of the sewage is 7.0, after 5 minutes of reaction at room temperature, it is found that the removal rate of sulfamethoxazole in the peracetic acid system activated by the single-atom cobalt catalyst is 100%. When the pH value of the sewage is 8.0, after 5 minutes of reaction at room temperature, it is found that the removal rate of sulfamethoxazole in the peracetic acid system activated by the single-atom cobalt catalyst is 92%. When the pH value of the sewage is 9.0, after 5 minutes of reaction at room temperature, it is found that the removal rate of sulfamethoxazole in the peracetic acid system activated by the single-atom cobalt catalyst is 76%. When the pH value of the sewage is 10.0, after reacting at room temperature for 5 minutes, it is found that the removal rate of sulfamethoxazole in the peracetic acid system activated by the single-atom cobalt catalyst is 46%. It can be determined that the peracetic acid system activated by the single-atom cobalt catalyst prepared by the present invention has a good removal effect on sulfamethoxazole in the pH range of 5.0 to 8.0, and both strong acidic and strong alkaline conditions are not conducive to the reaction.
[0087] 3. Degradation experiment with different catalyst addition amounts:
[0088] Peracetic acid was added to wastewater containing 10 μM sulfamethoxazole (SMX) to make its concentration reach 0.26 mM, and the pH value of the wastewater was adjusted to 7.0 with 0.1 mM sulfuric acid or 0.1 mM sodium hydroxide solution. The single-atom cobalt catalyst prepared in Example 1 was added to the above solution to make its concentration reach 25 mg / L, 50 mg / L, 75 mg / L, and 100 mg / L, respectively. The reaction was stirred at room temperature for 5 minutes, and the removal rate of sulfamethoxazole over time was recorded, as shown in FIG. Fig. 9 As shown. Fig. 9 It can be seen that when the concentration of the catalyst reaches above 50 mg / L, all SMX can be removed within 5 minutes.
[0089] 4. Degradation experiment with different amounts of peracetic acid added:
[0090] Peracetic acid was added to wastewater containing sulfamethoxazole (SMX) at a concentration of 10 μM to make its concentration reach 0.065 mM, 0.13 mM, 0.26 mM, and 0.52 mM, respectively, and the pH value of the wastewater was adjusted to 7.0 with 0.1 mM sulfuric acid or 0.1 mM sodium hydroxide solution. The single-atom cobalt catalyst prepared in Example 1 was added to the above solution to make its concentration reach 50 mg / L, and the reaction was stirred at room temperature for 5 minutes, and the removal rate of sulfamethoxazole over time was recorded, as shown in FIG. Fig.10 As shown. Fig.10 It can be seen that when the concentration of peracetic acid reaches above 0.26 mM, all SMX can be removed within 5 minutes.
[0091] 5. Degradation experiments on different pollutants:
[0092] Peracetic acid was added to wastewater containing 10 μM sulfadiazine (SDZ), sulfadimethoxine (SDM), sulfamethoxazole (SMIZ), ciprofloxacin (CIP), enrofloxacin (ENF), tetracycline (TTC), 4-chlorophenol (4-CP) and phenol (PN) to make the concentration reach 0.26 mM, and the pH value of the wastewater was adjusted to 7.0 with 0.1 mM sulfuric acid or 0.1 mM sodium hydroxide solution. The single-atom cobalt catalyst prepared in Example 1 was added to the above solution to make the concentration reach 50 mg / L, and the reaction was stirred at room temperature for 5 minutes. The removal rate of sulfamethoxazole over time was as follows: Fig.11 shown.
[0093] from Fig.11 It can be seen that in the system of peracetic acid activated by single-atom cobalt catalyst, after about 5 minutes, the removal rates of sulfadiazine (SDZ), sulfadimethoxine (SDM) and tetracycline (TTC) can reach 100%, the removal rates of enrofloxacin (ENF), 4-chlorophenol (4-CP) and sulfamethoxazole (SMIZ) can reach 97%, 97% and 92% respectively, and the removal rates of tetracycline (TTC) and phenol (PN) can reach 90%. The above results prove that the advanced oxidation technology of peracetic acid activated by nitrogen-sulfur co-doped single-atom cobalt catalyst has a high efficiency in the degradation of various antibiotics including sulfonamides, quinolones and tetracycline antibiotics.
[0094] 6. Cyclic performance of the nitrogen-sulfur co-doped single-atom cobalt catalyst of Example 1:
[0095] Peracetic acid is added to wastewater containing 10 μM sulfamethoxazole to make its concentration reach 0.26 mM, and the pH value of the wastewater is adjusted to 7.0 with 0.1 mM sulfuric acid or 0.1 mM sodium hydroxide solution. The single-atom cobalt catalyst prepared in Example 1 is added to the above solution to make its concentration reach 50 mg / L, and the reaction is stirred at room temperature for 5 minutes. The concentration of sulfamethoxazole during the reaction is measured, and its removal rate is calculated. The continuous cycle catalytic experiment of the catalyst is operated as follows: the solid catalyst after the reaction is collected by filtration, and it is repeatedly rinsed with deionized water for 3-5 times, and then placed in a vacuum drying oven at 60°C for drying. After that, the next catalytic reaction is started, and the cycle is repeated to measure the changes in pollutant degradation. The changes in the removal rate of sulfamethoxazole during the recycling of the catalyst are shown in Fig.12 .Depend on Fig.12 It can be seen that after four cycles, the 5-min removal rate of sulfamethoxazole in the system only decreased by about 8%, and its removal rate can still reach 92%, which shows that the single-atom cobalt catalyst prepared by the present invention has very good recyclability and is conducive to further promotion and application.
[0096] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a single-layer eggshell-shaped nitrogen-sulfur co-doped single-atom cobalt catalyst, characterized in that: The steps include: 1-allyl-2-thiourea and cobalt salt are dissolved in water, SiO2 nanospheres are added thereto, heated and stirred, and the precursor is obtained after evaporating the solvent; The precursor is calcined under the protection of an inert gas, SiO2 is etched after calcination, and then it is acid-leached, washed and dried to obtain the product.
2. The preparation method according to claim 1, characterized in that The cobalt salt is selected from cobalt nitrate, cobalt chloride or cobalt sulfate.
3. The preparation method according to claim 1, characterized in that: The molar ratio of the cobalt salt to 1-allyl-2-thiourea is 1:(15-35); the dosage ratio of the 1-allyl-2-thiourea to water is 1 g:(3-10) mL; and the mass ratio of the cobalt salt to SiO2 nanospheres is 0.08:(0.5-2).
4. The preparation method according to claim 1, characterized in that: The heating and stirring temperature is 60-90°C, and the heating and stirring time is 60-180 minutes; the evaporating solvent temperature is 50-70°C.
5. The preparation method according to claim 1, characterized in that: The calcination temperature is 850-1000° C., and the calcination time is 2-4 hours.
6. The preparation method according to claim 1, characterized in that: The method for etching SiO2 is to etch with sodium hydroxide or potassium hydroxide solution; The concentration of the sodium hydroxide or potassium hydroxide solution is 3 to 8 mol / L.
7. The preparation method according to claim 1, characterized in that: The acid leaching process uses hydrochloric acid or sulfuric acid solution with a concentration of 0.05-0.5 mol / L.
8. A single-layer eggshell-shaped nitrogen-sulfur co-doped single-atom cobalt catalyst prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the single-layer eggshell-shaped nitrogen-sulfur co-doped single-atom cobalt catalyst as claimed in claim 8 in activating peracetic acid to degrade organic pollutants.
10. The use according to claim 9, characterized in that The ratio of the single-layer eggshell-shaped nitrogen-sulfur co-doped single-atom cobalt catalyst, peracetic acid, and organic pollutants is (50-150) mg: (0.2-0.6) mmol: (1-15) μmol; the concentration of the single-layer eggshell-shaped nitrogen-sulfur co-doped single-atom cobalt catalyst is 50-150 mg / L.
Citation Information
Patent Citations
Nitrogen-doped carbon-based metal monoatomic catalyst as well as preparation method and application thereof
CN110124722A
Preparation method and application of sulfur coordination cobalt monatomic catalyst loaded by carbon-based carrier
CN114990567A
Persulfate catalytic material as well as preparation method and application thereof
CN117123224A
Sulfur and nitrogen co-doped carbon-loaded transition metal monatomic catalyst as well as preparation method and application thereof
CN117443421A
Magnetic monatomic cobalt catalyst and method for catalyzing peracetic acid to degrade antibiotics by using magnetic monatomic cobalt catalyst
CN117599794A